Analysis of Derivation Found in The Jakarta Post Headlines - Hadi , Muhammad Zaki Pahrul (Jurnal Ilmu Sosial dan Humaniora, 2023)
The term derivation has been defined as the formation of a new word or inflectable stem from another word or stem. It typically occurs by the addition of an affix. This study is a qualitative research on derivational morphemes entitled “a study of derivational morphemes used in The Jakarta Post headlines”. It answers the types of derivational morphemes in The Jakarta Post Headlines, aiming at finding their types and functions. Data of this research are qualitative in type and sentence containing derivational words taken from The Jakarta Post. In gathering the data, this research used metode simak (observing method). Extraingual method was used to analyze the data to find out the principles or rules of derivational morpheme types. This research shows that there are three types of derivational morphemes the most frequently used namely noun derived from verb, adjectives derived from verbs, adjectives derived from noun.